Planktonic Archaeal Ether Lipid Origins in Surface Waters of the North Pacific Subtropical Gyre - Li, Fuyan; Leu, Andy; Poff, Kirsten; Carlson, Laura T.; Ingalls, Anitra E.; DeLong, Edward F. (Frontiers in Microbiology, 2021)
Thaumarchaeota and Thermoplasmatota are the most abundant planktonic archaea in the sea. Thaumarchaeota contain tetraether lipids as their major membrane lipids, but the lipid composition of uncultured planktonic Thermoplasmatota representatives remains unknown. To address this knowledge gap, we quantified archaeal cells and ether lipids in open ocean depth profiles (0-200m) of the North Pacific Subtropical Gyre. Planktonic archaeal community structure and ether lipid composition in the water column partitioned into two separate clusters: one above the deep chlorophyll maximum, the other within and below it. In surface waters, Thermoplasmatota densities ranged from 2.11×106 - 6.02×106 cells/L, while Thaumarchaeota were undetectable. As previously reported for Thaumarchaeota, potential homologues of archaeal tetraether ring synthases were present in planktonic Thermoplasmatota metagenomes. Despite the absence of Thaumarchaeota in surface waters, measurable amounts of intact polar ether lipids were found there. Based on cell abundance estimates, these surface water archaeal ether lipids contributed only 1.21×10-9ng lipid/ Thermoplasmatota cell, about three orders of magnitude less than that reported for Thaumarchaeota cells. While these data indicate that even if some tetraether and diether lipids may be derived from Thermoplasmatota, they would only comprise a small fraction of Thermoplasmatota total biomass. Therefore, while both MGI Thaumarchaeota and MGII/III Thermoplasmatota are potential biological sources of archaeal GDGTs, the Thaumarchaeota appear to be the major contributors of archaeal tetraether lipids in planktonic marine habitats. These results extend and confirm previous reports of planktonic archaeal lipid sources, and further emphasize the need for Thermoplasmatota cultivation, to better characterize the membrane lipid constituents of marine planktonic Thermoplasmatota, and more precisely define the sources and patterns of archaeal tetraether lipid distributions in marine plankton.